Anti-PF4/polyanion antibodies in COVID-19 patients are associated with disease severity and pulmonary pathology. (19th May 2022) - Ueland, Thor; Hausberg, Ingvild; Mørtberg, Trude Victoria; Dahl, Tuva Børresdatter; Lerum, Tøri Vigeland; Michelsen, Annika; Ranheim, Trine; Nezvalova Henriksen, Katerina; Dyrhol-Riise, Anne Ma; Holme, Pål André; Aaløkken, Trond Mogens; Skjønsberg, Ole Henning; et al.
Abstract: Thromboembolic events are frequent and associated with poor outcome in severe COVID-19 disease. Anti-PF4/polyanion antibodies are related to heparin-induced thrombocytopenia (HIT) and thrombus formation, but data on these antibodies in unselected COVID-19 populations are scarce. We assessed the presence of anti-PF4/polyanion antibodies in prospectively collected serum from an unselected cohort of hospitalized COVID-19 patients and evaluated if elevated levels could give prognostic information on ICU admission and respiratory failure (RF), were associated with markers of inflammation, endothelial activation, platelet activation, coagulation and fibrosis and were associated with long-term pulmonary CT changes. Five out of 65 patients had anti-PF4/polyanion reactivity with OD ≥0.200. These patients had more severe disease as reflected by ICU admission without any evidence of HIT. They also had signs of enhanced inflammation and fibrinogenesis as reflected by elevated ferritin and osteopontin, respectively, during the first 10 days of hospitalization. Increased ferritin and osteopontin persisted in these patients at 3 months follow-up, concomitant with pulmonary CT pathology. Our finding shows that the presence of anti-PF4/polyanion antibodies in unselected hospitalized COVID−19 patients was not related to HIT, but was associated with disease severity, inflammation, and pulmonary pathology after 3 months.